Beginning of a journey: unraveling the mystery of chronic kidney disease of unknown aetiology (CKDu) in Sri Lanka - Jacob Kumaresan; Ruwanika Seneviratne (BMC, 2017)
Abstract Background Globally, chronic kidney disease of unknown aetiology (CKDu) is observed in several areas and among specific ethnic or occupational groups. Given the widespread environmental pollution and the proportions of agriculture workers world-wide, CKDu may be the next global public health issue demanding attention. Recent escalation of CKDu in Sri Lanka has caused a serious public health crisis in the country, made worse by lack of national data. Main text The specific geographic distribution, preponderance among farming population, similar histology findings and absence of usual risk factors for kidney disease indicate undetected nephrotoxic agents playing a role in causation. Some of the challenges for the country are uncoordinated preventive efforts, diverse opinions among stakeholders on causality and fragmented research efforts with limited focus on potential causes of CKDu. As a result, accurate estimation of the CKDu burden, identification of causative agents and implementation of effective actions have been delayed. Stakeholder engagement, with involvement of international experts has been the starting point for finalizing a working case definition to establish community based surveillance as a future platform to conduct long-term research. Conclusion The country is now poised to contribute to global knowledge by solving the mystery of 'u' in CKDu. This commentary highlights the importance and the mechanisms of making an effective breakthrough as early as possible; failing which CKDu can progress rapidly as demonstrated by the situation in Sri Lanka.